Pengaruh Intensitas Bermain Game Online Terhadap Konsentrasi Belajar Siswa di SMK Revany Indra Putra Kota Jambi - Syah Raihan Mullatifa; Akmal Sutja; Fellicia Ayu Sekonda (Departement of Mathematics Education, 2023)
The background of this research is that students spend more than 4 hours playing online mobile legends (ML) games a day. From the information obtained, students say that during certain lessons or certain teachers they will look for opportunities to play online games while the teacher is explaining the material, this is because students do not understand the material they are studying and it is very difficult for students to be able to concentrate when their minds are focused. on online games. This study aims to determine the effect of the intensity of playing online games on students' learning concentration. So that this research does not deviate from what is meant, it is limited in the intensity of playing online games seen from the length of access, psychological conditions and the purpose of playing. Meanwhile, the concentration of learning is limited from focusing attention, changing behavior, carrying out learning according to the objectives. This type of research is quantitative ex post facto. The population in this study were 50 students of class XI at Revany Indra Putra Vocational School, Jambi City, using a purposive sampling technique. Data analysis tools and techniques used the normality test, linearity test and simple regression analysis through SPSS 24. The results showed that the influence of the intensity of playing online games was categorized as high with a percentage of 70.84%, while learning concentration was in the medium category with a percentage of 58.75. %, as well as the influence of the intensity of playing online games on student learning concentration obtained in this study, namely 0.101 or 10.1%. This study shows a low but definite effect between the intensity of playing online games on the concentration of students at Revany Indra Putra Vocational School, Jambi City.